Ensino de arte visual contemporânea: desafios e implicações no contexto escolar - Valença, Kelly Bianca Clifford (2015)
The production of master’s theses and doctoral ones committed to the study of contemporary visual art at Brazilian educational context is still very scarce. It is important to enlighten that contemporaneity treated in this paper denotes, above all, a temporal position: it refers to the current facts and productions. Similarly, some studies also indicate that there is a few number of students – especially in basic education – who have access to the current artistic production through school. But what causes this? This thesis is configured as a qualitative investigation concerning a bibliographic research where the teaching of contemporary visual art composes the work universe. Analyzing the relation between the teaching of visual arts and the contemporary production of art, was the general objective of this study intending to answer the reason why this theme is uncommon from most of the Brazilian classrooms and what are the implications of this matter. Since the human condition and the phenomenon of perception are both in focus in this research, the results constructed were analyzed according to the Merleau-Ponty’s phenomenogical perspective. The relevance of this topic is justified by conceiving the artistic expression of the time lived as a possibility of comprehension and transformation of both the subjects and the world, which can make the contemporary art a potential teaching instrument.